Quality deterioration and loss of shelf life as a result of poor road conditions. (16th December 2019) - Pretorius, Cornelia J.; Steyn, Wynand J.v.d.M.
Postharvest science focuses mainly on the quality of fresh produce. One of the areas of interest is the shipment of tomatoes using road transport. Because tomatoes have a limited shelf life, it is vital to control the factors that lead to early deterioration of the quality of the product. Logistical operations can cause numerous forms of cuts and bruises on harvested tomatoes which compromise their quality and appearance. For this experiment, the in-transit conditions were monitored on trucks shipping tomatoes from three farms in Limpopo, South Africa to the fresh produce market in Pietermaritzburg. This research attempts to create a model that relates tomato damage and loss in shelf life to the road condition, fruit ripeness and position in the container. With this information in hand, logistic planners can make informed decisions during route planning. Transportation cost can be weighed against the cost of losses of produce during transportation. Similar models can be developed to include other types of fruits and vegetables.